Software-In-The-Loop Technique: An Approach To Support Reconfiguration Of Manufacturing System - Abdul Rahman, Azrul Azwan; Mohamad, Nor Rizan (Asian Research Publishing Network (ARPN), 2016)
Reconfiguration is one of the demands in most of manufacturing industries in order to support unpredictable global business market and to fulfill the various types of customer needs. A virtual commissioning is used as a tool to verify the control system in a simulation environment before the real system is developed. One of the techniques in virtual commissioning is Software-in-the-Loop (SIL). The benefits of SIL technique is it can estimate the real state of control system during the simulation stage. This paper presents the understanding of the SIL technique by using an implementation of the simulation based control system to support the reconfiguration of a manufacturing system. The result of the demonstration shows that the SIL technique has a potential to be used as a tool to configure the reconfiguration of the manufacturing system eventough the reaction time is slightly longer compared to the system simulation.